Feeding of the hungry by Jesus (Lk 9:10–17) as model for addressing the COVID-19 hunger challenge in Anambra State, Nigeria - Echeta, Uzonna F. (HTS teologiese studies, 2021)
Feeding of the hungry is a theologically significant miracle in the ministry of Jesus, little wonder it is recorded by all the gospel writers (Mathew, Mark, Luke and John). In Judaism, feeding the hungry and hearkening to the needs of the poor and vulnerable are core demands of the religion. In fact, such a service far outweighs any service that anyone could render to God. The hungry people, who Jesus attended to, are desperately hopeless and Jesus exemplified heightened selflessness, love and care. The coronavirus disease 2019 (COVID-19) hunger is very peculiar and severe. The hunger is a result of the lockdown of commercial activities, which paralysed businesses and grounded economic activities to a halt, and placed both the rich and the poor in the same boat. The appalling situation that prompted this research is that, whilst food and monetary donations are being made by concerned philanthropists, hungry people still abound in the state because of ineffective strategies in the sharing of the palliatives. This research adopted a historical–critical method of analysis and the new method in New Testament interpretation in interpreting the pericope (Lk 9:10–17). Focus was placed on the core text; parallel passages are compared to bring out the original meaning of the text and how it can be pragmatised in Anambra State. Results showed that Jesus effectively satisfied both the physical and spiritual hunger of the crowds (hoi ochloi). He was able to draw the attention of his disciples to the need to cater for the hungry; there is surplus and no wastage. Additionally, compassion, love and selflessness are seen to be important virtues needed for equitable distribution of aid to the poor. If Jesus’ strategies are adopted where applicable, Anambra State can be hunger-free.